A hidden rule in metal sulfide fullerenes: A case study of Sc2S@C88. Issue 19 (23rd June 2017) - Yu, Zi‐Yi; Lai, Han; Zhao, Wen‐Juan; Wu, Rui; Liu, Xue‐Sen; Gan, Li‐Hua
Abstract: To elucidate the structure of a compound is a necessary step for its practical applications. To study the structure and properties of metal sulfide fullerene Sc2 S@C88 detected by mass spectrometry, 11 194 isomers of C88 and 33 isomers of Sc2 S@C88 were systematically examined by density functional theory calculations. The calculations show that the two lowest‐energy isomers are Sc2 S@C88 :81 738 (IPR‐35) and Sc2 S@C88 :81 735 (IPR‐32), followed by Sc2 S@C88 :81 729 (IPR‐26), Sc2 S@C88: 81 712 (IPR‐9), and Sc2 S@C88: 81 733 (IPR‐30). Structural analysis shows that the first two energetically favored isomers are bridged by the third and fifth energetically favored isomers, which can transfer into each other via direct Stone–Wales rotation. The calculations of temperature effect show that the first two favored isomers become dominant forms of Sc2 S@C88 with decreasing temperature and may coexist in the soot. This structural convertibility among favored isomers of Sc2 S@C88 suggest a hidden rule that birds of a feather flock together in metal sulfide fullerenes. This rule may decrease the range of candidate cages for the structural identification of a metal sulfide fullerene. IR spectra are simulated for helping the future experimental identification of Sc2 S@C88 . Abstract : Density Functional Theory calculations are used to study the structure and properties of metal sulfide fullerene Sc2 S@C88 species, recently detected by mass spectrometry. It is found that the lowest‐energy isomers of Sc2 S@C88 can transform into each other via direct Stone–Wales rotation, suggesting that "birds of a feather flock together" in metal sulfide fullerenes. This theoretical approach provides a solid tool for the structural identification of metallofullerenes.